2014
DOI: 10.1002/clen.201300785
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Contribution and Associated Ecological Risk in the Coastal Zone Sediments of the Black Sea: Trabzon

Abstract: In this study, the natural and anthropogenic heavy metal (Cu, Pb, Zn, Ni, and Co) pollution in coastal sediments near the city Trabzon which exhibits an increasing population and industrial activity in the Southeastern Black Sea Region, were investigated spatially and temporally. The sediment along the coast of Trabzon is influenced by three rivers, Degirmendere, Yanbolu, and Solakli, resulting in a spatial separation. The highest heavy metal sediment concentrations were measured in the section influenced by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Cu, Cr, Co, and Ni included in the first group may be attributed to similar sources. Most studies reported that Cu, Cr, Co, and Ni can be primarily from industrial and urban activities, such as electrical machinery, chemical production, automobile exhausts, and waste incineration . Co is also used in fertilizer and agrochemical industry .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cu, Cr, Co, and Ni included in the first group may be attributed to similar sources. Most studies reported that Cu, Cr, Co, and Ni can be primarily from industrial and urban activities, such as electrical machinery, chemical production, automobile exhausts, and waste incineration . Co is also used in fertilizer and agrochemical industry .…”
Section: Discussionmentioning
confidence: 99%
“…I geo is calculated according to Eq. Igeo=normallog2true(Cn/1.5normal italicBntrue) where C n is the examined metals concentration in sediment samples and B n is the geochemical background concentration of the heavy metals. I geo values were interpreted as suggested by Varol , where, I geo ≤ 0 indicates unpolluted; 0–1 is unpolluted to moderately polluted; 1–2 is moderately polluted; 2–3 is moderately to heavily polluted; 3–4 is heavily polluted; 4–5 is heavily to extremely polluted; and >5 is extremely polluted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RI considers both toxicities and total content of toxic metals but not chemical speciation. In addition, I GEO , SQGs, and sediment guidance values are indices commonly used to determine the pollution load in the sediment layer of the aquatic environment . Although determination, spatial distribution, and enrichment of toxic metals in lake systems have been extensively discussed, very few researchers have focused on risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Lake sediments constitute a major part of aquatic reservoirs and play an important role in ecosystems. Heavy metals are absorbed and accumulated on surface sediments owing to their low solubility in the overlying water . These sediments may be considered as pollutant indicators as they can act as reservoir as well as carriers for the pollution in water bodies .…”
Section: Introductionmentioning
confidence: 99%